Aerobic and anaerobic contributions to energy production among junior male and female cross-country skiers during diagonal skiing - McGawley, K.; Holmberg, H. C. (International Journal of Sports Physiology and Performance, 2014)
Purpose: Cross-country-ski races place complex demands on athletes, with events lasting between approximately 3 min and 2 h. The aim of the current study was to compare the aerobic and anaerobic measures derived from a short time trial (TT) between male and female skiers using diagonal cross-country skiing. Methods: Twenty-four highly trained cross-country skiers (12 male and 12 female, age 17.4 ± 1.4 y, body mass 68.2 ± 8.9 kg, height 174 ± 8 cm) participated. The submaximal VO2-speed relationship and VO2max were derived from an incremental ramp test to exhaustion (RAMP), while the accumulated oxygen deficit (AOD), peak VO2, and performance time were measured during a 600-m TT. Results: The female skiers took longer to complete the TT than the males (209 ± 9 s vs 166 ± 7 s, P < .001) and exhibited a lower relative anaerobic contribution (20% ± 4% vs 24% ± 3%, P = .015) and a higher fractional utilization of VO2max (84% ± 4% vs 79% ± 5%, P = .007) than males. Although there was no significant difference in AOD between the sexes (40.9 ± 9.5 and 47.3 ± 7.4 mL/kg for females and males, respectively; P = .079), the mean difference ± 90% confidence intervals of 6.4 ± 6.0 mL/kg reflected a likely practical difference (ES = 0.72). The peak VO2 during the TT was significantly higher than VO2max during the RAMP for all participants combined (62.3 ± 6.8 vs 60.5 ± 7.2 mL/kg/min, P = .011), and the mean difference ± 90% confidence intervals of 1.8 ± 1.1 mL/kg/min reflected a possible practical difference (ES = 0.25). Conclusions: These results show that performance and physiological responses to a self-paced TT lasting approximately 3 min differ between sexes. In addition, a TT may provide a valid measure of VO2max.